Are more data always better for factor analysis? Results for the euro area, the six largest euro area countries and the UK - Giovanni Caggiano; George Kapetanios; Vincent Labhard (European Central Bank (ECB), 2009)
Factor based forecasting has been at the forefront of developments in the macroeconometric forecasting literature in the recent past. Despite the flurry of activity in the area, a number of specification issues such as the choice of the number of factors in the forecasting regression, the benefits of combining factor-based forecasts and the choice of the dataset from which to extract the factors remain partly unaddressed. This paper provides a comprehensive empirical investigation of these issues using data for the euro area, the six largest euro area countries, and the UK.
Keywords: C10; C15; C53; 330; Factors; Forecast Combinations; Large Datasets; Prognoseverfahren; Wirtschaftsprognose; Statistische Methode; Faktorenanalyse; Zeitreihenanalyse; Eurozone; Großbritannien